A Study of Teachers’ Satisfaction Toward School Administration in Rattanakosin Group Schools Under Bangkok Primary Education Service Area Office - Juntamin, Apinya (Legal State Journal, 2023)
This research article aims to study teachers’ satisfaction toward school administration in Rattanakosin group schools under Bangkok Primary Education Service Area Office and to compare teachers’ satisfaction toward school administration in Rattanakosin group schools under Bangkok Primary Education Service Area Office. Classified by education level, experience, and size of school. The samples used in the research 278 teachers. The instrument used to collect the data was a 5-point rating scale questionnaire. The discrimination was 0.80-1.00, and the reliability was 0.97. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation, t-test, One-Way ANOVA and Scheffe’ s comparison test. Findings are as follows: (1) The level of teacher’s satisfaction toward school administration in Rattanakosin group schools under Bangkok Primary Education Service Area Office were at a high level, as a whole aspect. (2) Teacher with different level of education, different level of experience, and different level size of school there were on teacher’s satisfaction toward school administration in Rattanakosin group schools under Bangkok Primary Education Service Area Office. Overall and each aspect were significant difference at the .05 level.